The gift of therapy : an open letter to a new generation of therapists and their patients - Yalom, Irvin D., 1931- (London : Piatkus, 2002)
Acclaimed author and renowned psychiatrist Irvin D. Yalom distills thirty-five years of psychotherapy wisdom into one brilliant volume. The culmination of master psychiatrist Dr. Irvin D. Yalom's more than thirty-five years in clinical practice, The Gift of Therapy is a remarkable and essential guidebook that illustrates through real case studies how patients and therapists alike can get the most out of therapy. The bestselling author of Love's Executioner shares his uniquely fresh approach and the valuable insights he has gained-presented as eighty-five personal and provocative 'tips for beginner therapists', including: Let the patient matter to you Acknowledge your errors Create a new therapy for each patient Do home visits (Almost) never make decisions for the patient Freud was not always wrong A book aimed at enriching the therapeutic process for a new generation of patients and counsellors, Yalom's Gift of Therapy is an entertaining, informative, and insightful read for anyone with an interest in the subject.